Rhetorical structure in Master of Arts (MA) research Proposals of Kenyatta University - Maroko, Geoffrey Mokua (Kenyatta University, 1999)
This study set out to investigate rhetorical structure (persuasion) in Master of Arts (MA) research proposals of Kenyatta University. This was by comparing the Kenyatta University Faculty of Arts (KUFA) model of proposal writing with the Create a Research Space (CARS) model of Research Article (RA) introductions which is claimed to epitomize rhetorical structure. The study also investigated if the presentation of the gist in the statement of the problem (Section 2A) in the KUFA model and citations in the KUFA proposal have particular linguistic signalling features which enhance rhetorical structure. This was an attempt aimed at contributing to research in Genre Analysis. A qualitative research design was used for this purpose. Data were drawn, from six randomly selected research proposals of the Academic Year 1997/98 in the Faculty of Arts and classified into two: textual and intuitional. These data were analyzed using the three theoretical approaches that guided this study namely: the Swales' (1990) CARS model of RA Introductions, Chubin and Moitra's (1975) Citation Typology and Thomas and Hawes' (1995) Citation as Persuasion .. The following findings emerged: • The KUFA model of proposal writing corresponds to the CARS model of RA introductions. • The gist in the statement of the problem (Section 2A) in the KUFA model is signalled by I' sets of linguistic features that enhance persuasion. • Citations in the KUFA research proposal may be classified into three: supplementary, negational and affirmative. They are marked by sets of linguistic features which enhance rhetorical structure. This study, consequently, recommends the need to use a genre-based teaching approach when instructing learners how to write a persuasive research proposal. Such an approach, it is believed, will enable the learner to enter a particular discourse community and learn how researchers organise research proposals.